Cultural Surgical of Indramayu-Cirebon Wayang Kulit Performance; Astrajingga Ngangsu Kaweruh - Sujati, Budi; Iryana, Wahyu; Mustofa, Muhamad Bisri (Universitas Islam Negeri Raden Intan Lampung, 2022)
The Wayang Kulit story in “The Astrajingga Ngangsu Kaweruh” play is very popular in the people of Indramayu and Cirebon, West Java. The people of Indramayu and Cirebon believe that the wayang culture was adopted from India as narrated in the stories of the Mahabharata and the Ramayana and then mixed and matched by the teachings of Raden Umar Said or Sunan Kalijaga into entertainment, spectacle as well as guidance. The guidance that makes people walk in the right direction is the guidance of faith based on the teachings of the religion that is rahmatan lil alamin, even though we all know that the story of the Mahabharata and the Ramayana are sacred books of Hinduism in India. While the spectacle is a show that makes the people of Indramayu-Cirebon entertained by the activity. Over time, the philosophical and historical values of the Indramayu and Cirebon shadow puppet shows, which were originally intended to broadcast Islam, were gradually used by the dalangs as entertainment venues such as weddings, circumcisions, and so on. Therefore, this paper tries to describe with a historical approach that the cultures that have existed since the Walisongo era must be preserved because a historical approach will know how important it is to care for and maintain this culture.